Media Ethnography in China – Ethics, Access and Interviews in a Non-Western Context (Global Media Journal - German Edition, 2022)
This paper is based on my PhD thesis about the production culture of Chinese entertainment. I will discuss the challenges I faced during my fieldwork in China and will reflect on a general level on how to access this non-western field for doing media ethnography. As a UK-based university researcher, doing ethnography in my own country, China, this brought me particular challenges. Some ethical guidelines in the UK were not applicable to issues concerning consent. Regarding this inapplicability, Chinese scholar Suiming Pan questioned the application of Western guidelines in a Chinese context: as sociology in China lacks local theories, should Chinese researchers apply Western theories in China or invent new theories based on phenomena that have never occurred in the West? By the same token, how should Chinese researchers adapt Western ethics guidelines? This paper aims to discuss these questions in the Chinese context – how I had to be flexible with guidelines while upholding academic standards. Since gaining access to Chinese media remains challenging, many compromises were made during the interactions with television production teams, gatekeepers and colleagues in the field. Furthermore, I encountered problems during my interviews with creative workers. Lastly, I will illustrate how I built relationships with people in the field and how I handled my identity crisis as an ethnographer in my own culture, hoping that my research experience can shed light on future ethnographic works in non-Western contexts.
Keywords: production studies; television production; ethnography; participant-observation; Chinese entertainment; non-western context; critical reflection